A survey on spatial variations of groundwater quality in Kabul, Afghanistan and its evaluation for different uses - Serajuddin Saed; Hadi Farhadian (علوم و مهندسی آبیاری)
Groundwater is one of the most important sources of freshwater supply in arid and semi-arid regions. The purpose of this research is to investigate the chemical quality of Kabul's groundwater using statistical description methods, statistical classification, quality indices, graphical methods, and also to examine the spatial variations of effective physicochemical parameters of 54 bore wells water using geostatistical methods with the help of GIS tools. The chemical quality evaluation shows that due to the influence of rivers on Kabul's groundwater, a large part of the city's groundwater quality is of the Mg-  and Mg-Ca-  types, which is considered inappropriate for industrial use based on the International Association of Hydrogeologists method . The United States Salinity Laboratory diagram shows that the groundwater in this city is in the average range, C3S1, and in some cases good and inappropriate for agricultural and irrigation purposes. In terms of drinking, according to the Schuler diagram, water quality is salty the groundwater in the region is categorized as brackish for drinking purposes, with moderate conditions in some areas. The spatial variations of key physicochemical parameters influencing the quality of Kabul's groundwater were analyzed using various interpolation methods. Then, using the mutual evaluation criterion, the best variogram model was selected to draw the estimation map. The results show that for the zoning of EC, TH, TDS, , , and  parameters, the inverse distance weighting method, and for , ,  the indicator kriging method were appropriate. The estimation maps of the spatial variations of effective parameters on Kabul's aquifers show that the groundwater quality is moderate towards the west of Kabul and becomes suitable as it progresses towards the west. In contrast, the quality of groundwater decreases from the center of the city towards the east, and the salinity of the water has increased.